Dampak Bangunan Sarang Burung Walet terhadap Masyarakat Kelurahan Tambun dan Kelurahan Nalu Kecamatan Baolan Kabupaten Tolitoli - Kahar, Kahar; Jawaria, Jawaria (Fakultas Peternakan Universitas Madako Tolitoli, 2024)
Swiftlet nest buildings are increasingly found in residential areas, including in Tambun and Nalu Sub-districts, Baolan District, Tolitoli Regency. This phenomenon has generated various community responses due to its social and environmental implications. This study aims to describe the community perception of the social and environmental impacts of swiftlet nest buildings. The research employed a descriptive qualitative method with 45 respondents selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results showed that most respondents were long-term residents who generally accepted the presence of swiftlet nest buildings because they provide economic benefits for both owners and the local area. However, some respondents expressed concern about noise disturbances and potential health risks, although odor problems were minimal due to regular cleaning conducted by the building owners. Overall, the community has shown social adaptation to the existence of swiftlet nest businesses, but better spatial regulation and environmental supervision are needed to minimize potential negative impacts in densely populated residential areas.